Risk Factors of Nonunion After Acute Osteoporotic Vertebral Fractures: A Prospective Multicenter Cohort Study. Issue 13 (1st July 2020) - Inose, Hiroyuki; Kato, Tsuyoshi; Ichimura, Shoichi; Nakamura, Hiroaki; Hoshino, Masatoshi; Togawa, Daisuke; Hirano, Toru; Tokuhashi, Yasuaki; Ohba, Tetsuro; Haro, Hirotaka; Tsuji, Takashi; Sato, Kimiaki; et al.
Abstract : Study Design: Prospective cohort study. Objective: To characterize a patient population with nonunion after acute osteoporotic vertebral fractures (OVFs) and compare the union and nonunion groups to identify risk factors for nonunion. Summary of Background Data: While OVFs are the most common type of osteoporotic fracture, the predictive value of a clinical assessment for nonunion at 48 weeks after OVF has not been extensively studied. Methods: This prospective multicenter cohort study included female patients aged 65 to 85 years with acute one-level osteoporotic compression fractures. In the radiographic analysis, the anterior vertebral body compression percentage was measured at 0, 12, and 48 weeks. Magnetic resonance imaging (MRI) was performed at enrollment and at 48 weeks to confirm the diagnosis and union status. The patient-reported outcome measures included scores on the European Quality of Life-5 Dimensions (EQ-5D), a visual analogue scale for low back pain, and the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ) at 0, 12, and 48 weeks. Results: In total, 166 patients completed the 12-month follow-up, 29 of whom had nonunion. Patients with nonunion at 48 weeks after OVF had lower EQ-5D and JOABPEQ walking ability, social life function, mental health, and lumbar function scores than those with union at 48 weeks after injury. The independent risk factors for nonunion after OVF in the acute phase were a diffuse low type pattern on T1-weighted MRI and diffuse low and fluid type patterns on T2-weighted MRI. The anterior vertebral body compression percentage and JOABPEQ social life function scores were independent risk factors at 12 weeks. Conclusion: A diffuse low type pattern on T1-weighted MRI and diffuse low and fluid type patterns on T2-weighted MRI were independent risk factors for nonunion in the acute phase. Patients who have acute OVFs with these risk factors should be carefully monitored for nonunion. Level of Evidence: 2 Abstract : This prospective multicenter cohort study investigated the predictive value of clinical and radiological findings for nonunion after osteoporotic compression fractures. A diffuse low type pattern on T1-weighted MRI and diffuse low and fluid type patterns on T2-weighted MRI were the independent risk factors for nonunion in the acute phase.